PENERAPAN MODEL PEMBELAJARAN PJBL DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ORGAN PERNAPASAN MANUSIA DI KELAS V SDN 3 BONE RAYA - Puspita Lamalundu; Abdul Haris Panai; Irvin Novita Arifin (STKIP Subang, 2024)
The problem statement of this research is whether the implementation of PJBL can improve learning outcomes in human organ respiratory materials of students in class V of SDN 3, Bone Raya. The purpose of this research is to improve the learning outcomes in human organ respiratory materials of students in class V of SDN 3, Bone Raya, through PJBL model. This is a classroom action research (PTK), using observation, tests, and documentation in collecting the data. The early observation shows that there were 5 out of 14 students (35.71%) who had achieved the Maximum Completion Criteria, while the other 9 (64.29%) had not. After cycle was applied, students who completed the criteria had reached to 42.86%, then continued to cycle II with the result of 85.71%. Therefore, it can be concluded that the learning outcomes of students in class V of SDN 3 of Bone Raya had improved.